(untitled) (Global Journal of Human-Social Science, 2022)
The war between the Longs and the Shorts is the backdrop for Eugène Ebodé’s Sovereign Magnificent. Told through the eyes of the eponymous character, Souveraine Magnifique, an orphan from the Longs’ ethnic group, she recounts the alarming circumstances of an atrocious war that sprang up between brothers of the same blood in the heart of a Rwanda ravaged by jealousy and unjustified hatred. How does fictional literature script this genocidal war by emphasizing the representation of an ethical value system in order to postulate an ethical worldview? Edmond Cros’s sociocriticism, through its two axes, the phenotext and the genotext, serves as a reading frame of reference to answer this question. On this basis, we revisit, in three points, the meaning of the chronotope that takes the place of a war scene; then the stylistic manoeuvres that allow us to visualize the literarity of the novel and, finally, the significant indices that inscribe the novelist’s argument in a humanist worldview.